Strategi Penguatan Ekonomi Syariah Melalui Wakaf Produktif di Kabupaten Bengkalis - Hakim, Lukman (PT. Riset Press International, 2023)
This study aims to examine strategies for strengthening the sharia economy through the management of productive waqf in Bengkalis Regency. A qualitative approach with a case study method was employed, involving in-depth interviews, participatory observation, and document analysis. The findings indicate that the management of productive waqf in Bengkalis still faces challenges, particularly in the capacity of nazhir (waqf managers), low public literacy regarding waqf, and the suboptimal utilization of natural resources and digital technology. These results align with previous studies emphasizing the importance of nazhir development and increased waqf literacy for effective productive waqf management. The research also identified a gap in the integration of natural resource utilization, digital technology, and capacity-building for nazhirs. Therefore, an integrated strategy is needed, involving institutional capacity strengthening, waqf literacy improvement, and the application of technology to support the sustainability of productive waqf, which contributes to the strengthening of the sharia economy and sustainable development. These findings are expected to serve as a reference for the development of waqf policies in similar regions.